A Systematic Review of the Spectrum of Cardiac Arrhythmias in Sub-Saharan Africa. Issue 1 (8th May 2020) - Yuyun, Matthew F.; Bonny, Aimé; Ng, G. André; Sliwa, Karen; Kengne, Andre Pascal; Chin, Ashley; Mocumbi, Ana Olga; Ngantcha, Marcus; Ajijola, Olujimi A.; Bukhman, Gene
Major structural cardiovascular diseases are associated with cardiac arrhythmias, but their full spectrum remains unknown in sub-Saharan Africa (SSA), which we addressed in this systematic review. Atrial fibrillation/atrial flutter (AF/AFL) prevalence is 16–22% in heart failure, 10–28% in rheumatic heart disease, 3–7% in cardiology admissions, but <1% in the general population. Use of oral anticoagulation is heterogenous (9–79%) across SSA. The epidemiology of sudden cardiac arrest/death is less characterized in SSA. Cardiopulmonary resuscitation is challenging, owing to low awareness and lack of equipment for life-support. About 18% of SSA countries have no cardiac implantable electronic devices services, leaving hundreds of millions of people without any access to treatment for advanced bradyarrhythmias, and implant rates are more than 200-fold lower than in the western world. Management of tachyarrhythmias is largely non-invasive (about 80% AF/AFL via rate-controlled strategy only), as electrophysiological study and catheter ablation centers are almost non-existent in most countries. Highlights: - Atrial fibrillation/flutter prevalence is 16–22% in heart failure, 10–28% in rheumatic heart disease, 3–7% in cardiology admissions, and <1% in the general population in sub-Saharan Africa (SSA). - Rates of oral anticoagulation use for CHA2DS2VASC score ≥2 are very diverse (9–79%) across SSA countries. - Data on sudden cardiac arrest are scant in SSA with low cardiopulmonary resuscitation awareness. - Low rates of cardiac implantable electronic devices insertions and rarity of invasive arrhythmia treatment centers are seen in SSA, relative to the high-income countries.